The Effect of Perceived Competence and Perceived Ease of Use on Continuance Intention with Perceived Enjoyment as a Mediating Variable - Sofia; Nur Afifah; Bintoro Bagus Purmono; Juniwati; Harry Setiawan (Journal of Educational Management Research, 2026)
The development of digital technology has accelerated the adoption of online learning platforms such as Duolingo in Indonesia. Despite its high level of popularity, the platform still faces challenges related to user retention and high churn rates. The inconsistency of previous research findings regarding the factors influencing continuance intention indicates a research gap that requires further investigation, particularly within the context of gamification-based learning applications. This study aims to analyze the effects of perceived competence and perceived ease of use on continuance intention, with perceived enjoyment serving as a mediating variable among Duolingo users in Indonesia. This research employed a quantitative approach with a causal design and involved 280 respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using Structural Equation Modeling (SEM) with AMOS. The results indicate that perceived competence and perceived ease of use have a positive and significant effect on perceived enjoyment and continuance intention. Furthermore, perceived enjoyment significantly mediates these relationships. These findings emphasize that the sustainability of learning application usage is influenced not only by cognitive factors but also by users’ affective experiences.